The Effect of Sales and Purchase Financing and Profit Sharing Financing on Financial Performance: Pengaruh Pembiayaan Jual Beli dan Pembiayaan Bagi Hasil Terhadap Kinerja Keuangan - Sari, Alieffia Finanda; Qudus, Nihlatul (Indonesian Journal of Innovation Studies, 2022)
Nowadays, the companies in the Islamic banking sector are growing, therefore there are many Islamic banking companies that compete in order to always benefit by providing credit benefits to the community. This study aims to examine the effect of buying and selling financing on the financial performance of companies in the Islamic banking sector. In this study using quantitative techniques through SPSS data processing tools, sampling based on criteria or purposive sampling so that there are 4 companies that are taken as research samples based on quarterly reports so that a sample of 48 financial statements is selected and contained in the predetermined criteria so that it is carried out calculation based on tabulation of data obtained. According to the results of the study, it was found that financial work could be influenced by buying and selling financing and profit sharing financing in Islamic banking sector companies on the IDX in 2018-2020. In this research, the result of the influence of determination is 63.8%.